CEREBRAL REVASCULIZATION IN PATIENTS OF 70 YEARS AND OLDER - A. N. Kosenkov; R. A. Vinogradov; I. A. Vinokurov (Acta Biomedica Scientifica, 2015)
The aim of the work was to evaluate the perioperative management of aged patients after elective surgical cerebral revascularization. We analyzed the outcomes of 813 patients of 70 years and older who had surgery for stenosis of the internal carotid artery [ІСА]. There were two groups: 392 patients who had carotid endarterectomy [CEA] and 421 patients who had the stenting. Age of the patients, severity of disease and comorbidity were similar in both groups In aged patients, the incidence of acute disorders of cerebral circulation (stroke] after CEA was significantly lower than the one after stenting (p = 0,04]. Frequency of perioperative myocardial infarction [MI] was 3 times higher in cases with CEA (p = 0,03]. in patients of 70 years and older, CEA shown lower incidence of stroke, however, there is increase of perioperative MI while using this method. Endovascular treatment could be chosen in patients with severe cardiac disease according to atherosclerotic plaques with no risk of embolism. In addition, the individual approach and assessment of social aspect are necessary.